Awake prone positioning for hypoxaemic respiratory failure: past, COVID-19 and perspectives. (5th May 2021) - Touchon, François; Trigui, Youssef; Prud'homme, Eloi; Lefebvre, Laurent; Giraud, Alais; Dols, Anne-Marie; Martinez, Stéphanie; Bernardi, Marie; Begne, Camille; Granier, Pascal; Chanez, Pascal; Forel, Jean-Marie; et al.
Prone positioning reduces mortality in the management of intubated patients with moderate-to-severe acute respiratory distress syndrome. It allows improvement in oxygenation by improving ventilation/perfusion ratio mismatching. Because of its positive physiological effects, prone positioning has also been tested in non-intubated, spontaneously breathing patients, or "awake" prone positioning. This review provides an update on awake prone positioning for hypoxaemic respiratory failure, in both coronavirus disease 2019 (COVID-19) and non-COVID-19 patients. In non-COVID-19 acute respiratory failure, studies are limited to a few small nonrandomised studies and involved patients with different diseases. However, results have been appealing with regard to oxygenation improvement, especially when combined with noninvasive ventilation or high-flow nasal cannula. The recent COVID-19 pandemic has led to a major increase in hospitalisations for acute respiratory failure. Awake prone positioning has been used with the aim to prevent intensive care unit admission and mechanical ventilation. Prone positioning in conscious, non-intubated COVID-19 patients is used in emergency departments, medical wards and intensive care units. Several trials reported an improvement in oxygenation and respiratory rate during prone positioning, but impacts on clinical outcomes, particularly on intubation rates and survival, remain unclear. Tolerance of prolonged prone positioning is an issue. Larger controlled, randomised studies are underway to provide results concerning clinical benefit and define optimised prone positioning regimens. In intubated ARDS patients, prone positioning reduces mortality. On spontaneously breathing patients, oxygenation improved during awake prone positioning. Relevant data on clinical outcomes are expected, especially on COVID-19 patients. https://bit.ly/2PU3B6v